THE EFFECTIVENES OF E-LEARNING AS A LEARNING MEDIA IN ARCHIVING SUBJECT AT SMKN 2 BUDURAN SIDOARJO DURING THE COVID-19 PANDEMIC - Yuni Maulidiyah Dwi Fajar; Durinda Puspasari (JURNAL PAJAR (Pendidikan dan Pengajaran), 2021)
This study aimed to analyze the effectiveness of e-learning as a learning media for archiving subjects at SMKN 2 Buduran Sidoarjo in the covid-19 pandemic. This study was qualitative research. Data were collected through interviews and questionnaires. The validity of data was examined by source triangulation. Then, the data were analyzed by the Miles and Huberman Model, namely data collection, data reduction, data presentation, and conclusions. The results showed that e-learning learning media was effectively utilized in the archiving subject, based on 4 indicators of learning effectiveness. In terms of the elearning quality, which was seen from the process and results, it was found that 2 applications used during the learning process, namely google classroom and whatsapp was easily accessed and understood. In addition, the students’ learning outcomes, which was scored more than 80 (72.6%); described the student’ and teachers’ readiness in starting the lessons and the ongoing process of learning, such as the fulfillment of facilities like cellphones and laptops, after that, the teachers provided materials for students to learn first. Moreover, in terms of incentives, the teachers’ activities whcih motivated students every time they started the lessons included giving advices and positive energy; the teachers provided additional score for active students. Then, in terms of time, it was seen from the presence of  teacher to start the lesson on time in which the teachers assigned students based on the predetermined deadlines so that the students were more disciplined.